Mangrove Diversity in Pare Mas Jerowaru, East Lombok - Herlita, Mesi; Idrus, Agil Al; Syukur, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The purpose of study is to determine the diversity of mangrove species in Pare Mas Jerowaru East Lombok. Data collection in this study was carried out using the drone check method and a combination of line and square transect methods measuring 2 x 2 m (seedling category), 5 x 5 m (pile category), 10 m x 10 (pole category), and 20 m x 20 m (tree category). Data analysis was carried out by calculating frequency, density, closure area, important value index, Shanon-Wiener diversity index (H'), uniformity index and dominance index. Mangrove species found in the mangrove area in Pare Mas are 233 individuals, consisting of 3 species belonging to 3 families. The value of mangrove species diversity index in mangrove area in Pare Mas, Jerowaru, East Lombok is 0.743, uniformity index value is 0.676, dominance index value is 0.507, of 3 research transects of Rhizophora Apiculata and Sonneratia Alba species have highest frequency value of 0.8 ind/m². The highest density is owned by seedling category of 1,708 ind/m2, followed by sapling category of 1,187 ind/m2. Conclusion that the value of the mangrove species diversity index in Pare Mas Village is in the low category of 0.743. The highest species diversity index was found in transect 2 with a diversity index value of 0.797 and lowest in transect 3, which was with a value of 0.642.